Figure 2 from: Pezzani R (2016) Saxifraga aizoides extract: novel potential effects on tumor cell models. Research Ideas and Outcomes 2: e9632. https://doi.org/10.3897/rio.2.e9632 - Pezzani, Raffaele (Zenodo, 2016)
Figure 2 - Saxifraga aizoides: the characteristic yellow flowers punctuated by orange spots on the petals.